Challenges experienced by mothers caring for children with cerebral palsy in Zambia - Carol Singogo; Margaret Mweshi; Anthea Rhoda (AOSIS, 2015)
Background: Mothers caring for children with disability experience a number of challenges. Aim: The aim of the study was to explore the challenges that mothers who cared for children with cerebral palsy (CP) living in Zambia experienced. Methods: During a qualitative study the experiences of 16 conveniently sampled mothers of children with CP, from the Ndola district in Zambia, were explored by means of interviews. The responses were thematically analysed. All the necessary ethical considerations were upheld. Results: Mothers experienced social isolation and marital problems, as well as negative attitudes from family, friends, community members and health care professionals. The physical environment created access challenges because of a lack of sidewalks, ramps, functioning lifts and small indoor spaces. Conclusion: Mothers of children with CP feel socially isolated owing to a lack of support from family, community members, and health care providers. This social isolation was exacerbated by attitudes of others towards the mothers; it was felt that mothers were responsible for their children's condition. Mothers also experienced marital problems as a result of having a child with CP.